[Debating The Capitalist Threat - Part 3]
The continuation of "The Capitalist Threat" conference held on June 22, 1998 at the Hungarian Academy of Sciences. Contains the second part of Ferenc Rabár's (Budapest University of Economic Sciences) comments. The last speaker is Jörn Rüsen (Kulturwissenschaftliches Institut, Essen) and his speech is followed by Soros' concluding remarks.